Moral Drift and the American Psychological Association: The Road to Torture - Welch, Bryant L. (Social justice, 2010)
The article focuses on the efforts of the American Psychological Association (APA) to support the U.S. government in using torture in the War on Terror. Topics include the use of psychological expertise by the administration of U.S. President George W. Bush to justify torture of detainees, ethical questions surrounding the involvement of APA psychologists in U.S. interrogations, and the lack of leadership in the APA to speak out against torture. It is suggested that APA psychologists did not think independently from the U.S. military and followed the Bush administration in supporting torture.